Correlation between spot urine protein creatinine ratio and 24-hour urinary protein in systemic lupus erythematosus patients with proteinuria - Joshi, Kushai Raj; Paudyal, Buddhi Prasad; Chimariya, Samipa; Panthi, Ram Chandra; Dhungana, Milan; Bidari, Subodh Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: All patients with Systemic Lupus Erythematosus(SLE) should be evaluated for proteinuria. Twenty-four hour urinary protein (24hUP) is the gold standard to quantify proteinuria but is cumbersome and is sometimes inaccurate. Spot urine protein creatinine ratio (UPCR) is a simple, convenient method to quantify proteinuria. This study aims to analyse its utility as a screening tool and ability to accurately measure proteinuria against 24 hUP was determined. Method: This was a cross sectional study. Eighty-seven patients with lupus with proteinuria on urinalysis were enrolled. Proteinuria was quantified using UPCR and 24 hUP. A prospective, analytical and observational study was done for a year. Sensitivity, specificity, correlation and agreement analysis between UPCR and 24 hUP was done. The best cutoff points for UPCR predicting a 24 hUP of 0.5, 1.0 and 3.0 g/day were determined using receiver operating characteristic curve. Result: The Sensitivity and specificity of UPCR were 97% and 29.1%, respectively. All samples’ correlation was high but negligible to low at lower range proteinuria, i.e.≤ 3gram/day and high at >3 g/day. Agreement for all samples, as well as for different levels of proteinuria, was poor. Cutoff points for optimal sensitivity and specificity of UPCR predicting 24hUP of 0.5, 1.0, and 3 g/day was 0.8, 1.55, and 4.5 g/g, respectively. Conclusion: With sensitivity of 97%, UPCR can be used as a screening test for proteinuria. However, due to poor specificity of UPCR and poor agreement, the accurate level of proteinuria should be measured by 24hUP.